2020
DOI: 10.1002/jmri.27080
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of PI‐RADS Version 2 and 2.1 in Transition Zone Lesions for Detection of Prostate Cancer: Preliminary Experience

Abstract: BackgroundThere appears to be less agreement in the identification of cancers in the transition zone (TZ), which is not as reliable as those in peripheral zone when using the Prostate Imaging Reporting and Data System (PI‐RADS) version 2 (v2). In response to such shortcomings, the updated version 2.1 was introduced, which incorporated diffusion‐weighted imaging (DWI) into category 2 and clarified lexicons.PurposeTo compare the diagnostic performance for the detection of clinically significant TZ prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 33 publications
5
56
2
3
Order By: Relevance
“…One of the major modifications in version 2.1 is the diagnostic criteria for the transitional zone PCa of low T2WI scores. When comparing the performance between version 2 and 2.1 for characterization of suspected PCa, several studies suggested that AUC tended to be higher in version 2.1 than in version 2 without statistical significance ( 6 8 ). It must be noted that PI-RADS v2.1 still showed a high false positive rate (moderate specificity) for PCa diagnosis, similar to that with PI-RADS v2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major modifications in version 2.1 is the diagnostic criteria for the transitional zone PCa of low T2WI scores. When comparing the performance between version 2 and 2.1 for characterization of suspected PCa, several studies suggested that AUC tended to be higher in version 2.1 than in version 2 without statistical significance ( 6 8 ). It must be noted that PI-RADS v2.1 still showed a high false positive rate (moderate specificity) for PCa diagnosis, similar to that with PI-RADS v2.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, version 2 was described to further improve reporting accuracy, and now has seen a broad uptake ( 4 , 5 ). In 2019, PI-RADS version 2.1 was newly described, with several studies suggesting that version 2.1 could be preferable than version 2 for the evaluation of transition zone PCa ( 6 8 ). PI-RADS is now playing an increasingly prominent role in PCa diagnosis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since, PI-RADS 3 does not identify the same risk of cancer in different prostate zones, the predictive value of PI-RADS 3 should be considered as low in the TZ respect to PZ. However, the estimating of the predictive value of PI-RADS 3 lesions has methodological bias because it do not represent the primary endpoint of published studies, (58). Their results demonstrated that the last version has both higher sensitivity and specificity for the overall detection of PCa for category higher than 3 lesions, independently of the prostatic zone.…”
Section: Focus On Pi-rads 3 Lesions In the Tz Vs Pzmentioning
confidence: 99%
“…However, since the κ values depend on many factors (including the prevalence of disease) [28], it makes no sense to compare κ value obtained in different studies. To account for this, PI-RADS v2 and 2.1 scoring should both be assigned on the same group of patients, as done in recent studies by Tamada et al and Byun et al [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the recent introduction of PI-RADS v2.1, studies evaluating its accuracy are few [24,25], and none of these aims to investigate the actual value of DCE for the PI-RADS assignment of PCa lesions.…”
Section: Introductionmentioning
confidence: 99%